Inside Cover: Boron Complexes of Glyoxal‐Derived Ugi Adducts as a New Class of Aggregation‐Induced Emission Photoluminescent Materials (Chem. Asian J. 8/2017). Issue 8 (28th March 2017) - Wei, Huiping; Wang, Gaigai; Wang, Yingchun; Li, Binbin; Huang, Jianjun; Kashtanov, Stepan; Van Hecke, Kristof; Pereshivko, Olga P.; Peshkov, Vsevolod A.
Abstract : Shine bright like a dAIEmond ! A series of new O, O‐chelated boron complexes has been prepared through a four‐component Ugi reaction followed by the complexation of the resulting 1, 3‐dicarbonyl compounds with boron trifluoride diethyl etherate. The optical properties of these novel luminophores have been assessed, revealing pronounced aggregation‐induced emission (AIE) features. The photoluminescence quantum yields for the solid samples were observed in the range of about 0.80–1.00, placing them among the most efficient boron‐based luminophores. More information can be found in the Communication by Vsevolod A. Peshkov, Olga P. Pereshivko et al. onpage 825 in Issue 8, 2017 (DOI:10.1002/asia.201700051 ).